If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -26 = 5y + -6 Reorder the terms: -26 = -6 + 5y Solving -26 = -6 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -26 + -5y = -6 + 5y + -5y Combine like terms: 5y + -5y = 0 -26 + -5y = -6 + 0 -26 + -5y = -6 Add '26' to each side of the equation. -26 + 26 + -5y = -6 + 26 Combine like terms: -26 + 26 = 0 0 + -5y = -6 + 26 -5y = -6 + 26 Combine like terms: -6 + 26 = 20 -5y = 20 Divide each side by '-5'. y = -4 Simplifying y = -4
| 6x^2+35x+33=0 | | 8x+47=8[x+5] | | 12x-18=15x | | 6x^2-35x-33=0 | | 100+1x=5x-1 | | -3i/7=-7/8 | | (5y^3-2y^2)(-35y+14)=0 | | 2(5x+7)=24 | | 6f+10=2f-30 | | 18-7f=-9 | | 10x+600=664 | | 7x/8=-10 | | 14b=16b+8 | | X-(-16)=16 | | (8X-5)-(3X-3)=0 | | 48=16s | | -5x-9=-24 | | 1=w-4 | | 6c+4=c+24 | | -5l/9=25 | | 5x+7=-33 | | x^4-6x^2-2=0 | | 45+1.99m=68.88 | | 7p+4=-2+p | | 2W^2+11w+5=0 | | .1(x)+.15(10)=.12(x+15) | | 4x+9=-23 | | -(3x-1)=2(x-2) | | -2k+7=5k | | -5(t-2)-(t+4)=8 | | -7(0.2x+0.3)-3.9=-0.4 | | 2n/3=-12 |